2010
DOI: 10.1158/0008-5472.can-09-4167
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Trichloroethylene Exposure and Renal Carcinoma Risk: Evidence of Genetic Susceptibility by Reductive Metabolism Gene Variants

Abstract: Trichloroethylene (TCE) is a suspected renal carcinogen. TCE-associated renal genotoxicity occurs predominantly through glutathione S-transferase (GST) conjugation and bioactivation by renal cysteine β-lyase (CCBL1). We conducted a case-control study in Central Europe (1,097 cases and 1,476 controls) specifically designed to assess risk associated with occupational exposure to TCE through analysis of detailed job histories. All jobs were coded for organic/chlorinated solvent and TCE exposure (ever/never) as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 38 publications
3
89
1
6
Order By: Relevance
“…Additionally, positive exposureresponse relationships were reported in several case-control (Charbotel et al, 2006;Moore et al, 2010) and cohort studies (Zhao et al, 2005;Raaschou-Nielsen et al, 2003) using different exposure metrics. In Moore et al (2010), statistically significant associations between occupational exposure to TCE and renal cell carcinoma were only observed in individuals with an active GSTT1 genotype and certain CCBL1 genotypes. Two metaanalyses (Scott and Jinot, 2011;Karami et al, 2012) support the observations from individual studies, reporting an approximately 30% increased risk of kidney cancer associated with TCE exposure as well as a positive exposure-response relationship.…”
Section: Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, positive exposureresponse relationships were reported in several case-control (Charbotel et al, 2006;Moore et al, 2010) and cohort studies (Zhao et al, 2005;Raaschou-Nielsen et al, 2003) using different exposure metrics. In Moore et al (2010), statistically significant associations between occupational exposure to TCE and renal cell carcinoma were only observed in individuals with an active GSTT1 genotype and certain CCBL1 genotypes. Two metaanalyses (Scott and Jinot, 2011;Karami et al, 2012) support the observations from individual studies, reporting an approximately 30% increased risk of kidney cancer associated with TCE exposure as well as a positive exposure-response relationship.…”
Section: Cancermentioning
confidence: 91%
“…An increased risk of kidney cancer was reported in all of the studies in which there was a moderate to very high level of estimated TCE exposure (Henschler et al, 1995;Morgan et al, 1998;Vamvakas et al, 1998;Brüning et al, 2003;Raaschou-Nielsen et al, 2003;Zhao et al, 2005;Boice et al, 2006;Charbotel et al, 2006;Radican et al, 2008;Moore et al, 2010;Hansen et al, 2013), with most risk estimates being statistically significant. Additionally, positive exposureresponse relationships were reported in several case-control (Charbotel et al, 2006;Moore et al, 2010) and cohort studies (Zhao et al, 2005;Raaschou-Nielsen et al, 2003) using different exposure metrics. In Moore et al (2010), statistically significant associations between occupational exposure to TCE and renal cell carcinoma were only observed in individuals with an active GSTT1 genotype and certain CCBL1 genotypes.…”
Section: Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…GSTT1 in bioactivation of various cancerogenic compounds, such as trichloroethylene (Moore et al 2010). Indeed, our group has showed that GSTT1-active genotype is associated with TCC risk in men exposed to pesticides .…”
Section: Smoking Habitsmentioning
confidence: 94%
“…As a consequence, TCE has been detected in the blood of a large number of nonoccupationally exposed adults (Churchill et al, 2001;Blount et al, 2006). Concern was raised about possible long term health effects of TCE and a number of epidemiology studies has suggested links between TCE exposure and an increased incidence of tumours at a number of sites (Moore et al, 2010;Scott and Chiu, 2006;Scott and Jinot, 2011;Wartenberg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%